ANALISIS EFISIENSI BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) WILAYAH JABODETABEK DENGAN PENDEKATAN TWO STAGE DATA ENVELOPMENT ANALYSIS (DEA) - Naufal, Fadhil Muhammad; Firdaus, Achmad (EQUILIBRIUM, 2017)
This research aims to measure the level of technical efficency of Bank Pembiayaan Rakyat Syariah (BPRS) in Jabodetabek Region during the period 2015-2016. This is quantitative reasearch. Data used in this research was a secondary data, collected from financial report from Bank Indonesia and Otoritas Jasa Keuangan. The sampling technique that issued in this research was purposive sampling with taking 12 samples of BPRS. Efficiency measurement in this research used non-parametric statistic Data Envelopment Analysis (DEA) with the intermediation approach. The results showed that 12 BPRS in Jabodetabek Region during the 2015-2016 period as whole has  a  fluctuating level of efficiency. Meanwhile, the second phase of testing using Tobit methods shows that internal factor, CAR, has significant impact on BPRS efficiency in Jabodetabek.